Karakter Spasial dan Arahan Awal Penataan Kawasan Pecinan Manado Berbasis Urban Heritage - Tiara Millenia Loziska; Sitti Rahma Sy. Wahab; Reny Kartika Sary (Arsir: Jurnal Arsitektur, 2026)
Manado Chinatown has an urban heritage character shaped by its commercial corridor, shophouses, Chinese temples, and continuing cultural activities. Facade alterations, limited open space, parking conflicts, and inadequate pedestrian conditions may weaken the district’s spatial legibility. This study identifies the principal spatial characteristics and physical issues and formulates preliminary planning directions based on urban heritage. The findings indicate a compact urban structure in which built mass accounts for approximately 87% of the study area, a linear mixed-use pattern, D.I. Panjaitan Street as the primary path, and Chinese temples as the principal landmarks. The main issues are limited open space, pedestrian obstructions, on-street parking, and visual alterations to building facades. The preliminary directions include strengthening the continuity of the heritage corridor, improving basic pedestrian conditions, managing parking and residual spaces, and controlling the visual character of buildings. These findings provide initial input for physical planning rather than final implementation plan.